Granulocyte concentrate splitting does not affect phenotype and function. Issue 2 (15th December 2022) - Koo, Sebastian; Offner, Robert; Haile, Sophie‐Marie; Brosig, Andreas; Hähnel, Viola; Gruber, Michael; Burkhardt, Ralph; Ahrens, Norbert
Abstract: Background: More granulocyte concentrates (GCs) could be produced for more patients from the same donor if apheresis bags were split and stored for longer periods of time. Hence, we tested the hypothesis that splitting and extension of storage of GCs do not impair granulocyte function or viability. Study Design and Methods: Granulocyte apheresis concentrates were produced using modified fluid gelatin as a separation enhancer, split into two portions, and stored for 24 and 48 h. Granulocyte function, represented by cell migration, reactive oxygen species (ROS) production, and neutrophil extracellular trap formation (NETosis), was measured by live‐cell imaging. ROS production, adhesive surface protein expression, and viability were measured by flow cytometry. Results: Splitting had no effect on any of the tested parameters. After 24 h of storage, live‐cell imaging showed no significant difference in migration, time to maximum ROS production, time to half‐maximum NETosis, viability, or CD11b expression, but ROS production induced by phorbol 12‐myristate 13‐acetate (PMA) decreased from an initial median fluorescence intensity of 1775–590 artificial units. After 48 h, PMA‐induced ROS production, viability, and migration declined, as reflected by decreases in median total distance (119 vs. 63.5 μm) and median Euclidean distance (30.75 vs. 14.3 μm). Conclusion: Splitting GC products has no effect on granulocyte viability or function, but extended storage >24 h does compromise granulocyte function. The findings confirm that GCs should be transfused within 24 h of collection. Longer storage cannot be recommended.